The ancient history of the Egyptians, Carthaginians, Assyrians, Babylonians, Medes and Persians, Macedonians and Grecians and Macedonians - Rollin, Charles (G. Cowie and Co., 1827)
The Ancient History of the Egyptians, Carthaginians, Assyrians, Babylonians, Medes and Persians, Macedonians and Grecians (Vol. 1 of 6) is presented here in a high quality paperback edition. This popular classic work by Charles Rollin is in the English language, and may not include graphics or images from the original edition. If you enjoy the works of Charles Rollin then we highly recommend this publication for your book collection.